GENDER DIFFERENCES IN COGNITIVE FUNCTIONS IN PATIENTS WITH PARANOID CHIZOPHRENIA - Herasymenko, L. (World of Medicine and Biology, 2016)
Neurocognitve deficit has consequences in the implementation of everyday actions, social responsibilities and professional duties. Taking into account gender differences of cognitive impairment, suffering from paranoid schizophrenia is reasonable and clinically appropriate. The results of the study can be taken into account in the preparation of individual therapeutic, rehabilitation and prevention programs, because they are based on statistically significant differences in clinical and social characteristics of women and men.
Keywords: paranoid schizophrenia; cognitive disorders; gender differences